Dilema Pengawasan Gardu Partisipatif Pemilukada: (Studi Tentang Efektifitas Pengawasan Partisipatif Pemilihan Gubernur Dan Wakil Gubernur Provinsi Kepulauan Bangka Belitung Tahun 2017) - Ranto Ranto; Mohammad Rafli Abbas (Journal of Politics and Policy, 2019)
This study aims to explain how far the effectiveness of participatory election-based supervision took place in the election of Governors and Deputy Governors of the 2017 Bangka Belitung Islands Province. The debate is becoming more and more complexes and more complexes when the idealism of the existing surveillance system collides with the real context of the field of reality. The problem will become so complicated when the theoretical conceptual building fails to explain and even becomes a guide in engineering its ideal political reality. To conduct these study qualitative descriptive research methods will be used. Primary data sources will be obtained through non-participant observation and in-depth interviews whose information is determined by purposive sampling. To help analyze this study, the theory of participatory supervision will be used which includes electoral reform and local democracy, contextualization of participatory engagement. Data analysis techniques are carried out with the stages of collecting, reducing, displaying and drawing conclusions.